Analysis of Mucin glycoprotein expression in colorectal cancer - Tarkiainen, Vilma (2023)
Colorectal cancer is a global problem and one of the leading causes of cancer-associated deaths. It is diagnosed with standard classification based on the tumour node metastasis classification system provided by the Union for International Cancer Control and the American Joint Committee on Cancer. In many cases, colorectal cancer is detected in advanced stages, and the prognosis is usually less favourable compared to if the cancer had been diagnosed in earlier stages. Although clinicopathological staging predicts the patient’s survival relatively well, some patients would benefit from more precise estimation. Thus, there is a need for finding novel prognostic markers to advise treatment decisions towards personalized medicine. In this thesis, the expression of mucins in colorectal cancer was studied. Mucins are glycoproteins that have essential roles in epithelial tissues, such as cell signalling and the formation of protective barriers. Aberrant expression of some mucins in colorectal cancer is found to be associated with cancer progression. In this work, the expression of five mucins: MUC1, MUC2, MUC4, MUC5AC and MUC6 was analysed. The expression was studied using immunohistochemistry staining. Associations between mucins and clinicopathological factors and colorectal cancer survival were assessed. MUC1 protein was the most prominent factor related to the prognosis, and higher cytoplasmic expression of MUC1 was associated with worse survival in multiple analyses. In addition, higher cytoplasmic expression of MUC4 was associated with worse survival. These results indicate that MUC1 and MUC4 could be considered prognostic markers in colorectal cancer. In addition, Fourier transform infrared (FTIR) spectroscopy was used to determine whether the normal colon and cancerous tissue could be distinguished based on spectra. Spectroscopic analysis was conducted for normal colon, mucinous colorectal cancer, and colorectal cancer. Some differences in the spectra between tissue types were detected. This study demonstrated that FTIR spectroscopy could be potentially used for cancer research. However, as a diagnostic method, FTIR spectroscopy needs further validation.